Development of a Mock Extracorporeal Membrane Oxygenation Circuit to Assess Recirculation. Issue 4 (July 2016) - Jayewardene, Ishanth Devinda; Xie, Ashleigh; Iyer, Arjun; Pye, Roger; Dhital, Kumud
Abstract : A limitation of veno-venous extracorporeal membrane oxygenation (VV-ECMO) is the recirculating of newly oxygenated blood back to the VV-ECMO circuit. We compared cannulation strategies for combating recirculation utilizing a mock circulation loop (MCL) with ultrasonic flow probes and pressure transducers ensuring that the MCL was run at physiological hemodynamic parameters. Mean recirculation percentages were lower (ANOVA, F = 14.25; p = 0.0001) with the Wang-Zwische dual lumen cannula (4.00 ± 1.77, n = 7) than both the femoro-jugular (15.23 ± 7.00, n = 8) and the femoro-femoral cannulation configurations (13.49 ± 1.44, n = 8).